Diffability Reflected in Danielle steel's Winners (2013) Novel: An Individual Psychological Approach - Marganingtyas, Alfi Rosida, Dr. Phil. Dewi Chandraningrum, M. Ed, Titis Setyabudi, S.S. M. Hum (2015)
The major problem of this study is diffability. Someone who suddenly gets a diffability, she must experience a big change in her life. The objective of this study is to analyze Danielle steel's Winners based on the structural elements and analyze this novel based on the Individual Psychological Approach. The Writer employs qualitative method. The writer uses two data sources: primary and secondary. The primary data source of the study is Winners novel by Danielle Steel. Secondary data are the supporting data taken from literary books, criticism, and some articles related to the novel. The secondary data of the study are taken from any information related to the novel. The method of data collection is the researcher will employ the descriptive qualitative research. Based on the analysis, the researcher gets some conclusions. The study shows that the problem faced by the major character is her diffability. It is proven by her dream that becomes obstructed. She is a skier. She wants to be a winner of ski Olympic. Suddenly, she gets diffability because an accident. She gets spinal cord injury. She lose the function of her legs. She must sit in a wheelchair.